EARLY DIAGNOSIS OF PURULENT FORMS OF ACUTE PYELONEPHRITIS - Qo’ziyev Sohib Saloyiddin o’g’li (KONFERENSIYALAR, 2025)
Аnnotation. This article provides an overview of one of the most relevant topics  in  modern  urology  –  the  early  diagnosis  of  purulent  forms  of pyelonephritis.  It  presents  the  current  state  of  the  issue  and  highlights  the  key debatable  aspects  of  the  problem.  The  article  reviews  nearly  all  non-invasive imaging  methods  for  diagnosing  various  forms  of  purulent  pyelonephritis, demonstrating their capabilities, advantages, and limitations.